2021
DOI: 10.3390/ijerph18094851
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Dietary Intake among Rural Indian Women: An Exploratory Study

Abstract: Food insecurity is an important contributor to health and a factor in both underweight and malnutrition, and overweight and obesity. Countries where both undernutrition and overweight and obesity coexist are said to be experiencing a double burden of malnutrition. India is one example of a country experiencing this double burden. Women have been found to experience the negative impacts of food insecurity and obesity, however, the reasons that women experience the impact of malnutrition more so than men are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…According to Sinclair et al, rural women had a higher prevalence of FI, which is in accordance with our subgroup analyses based on the region that indicated that the prevalence of FI was higher in rural areas [66.1% (95% CI: 58.8–73.4%)] compared to urban areas [47.1% (95% CI: 58.8–73.4%)] ( 136 ). Another study conducted by Sims et al found that there was FI and malnutrition among Indian rural women ( 137 ). In addition, Sansón-Rosas et al found high rates of FI in Colombian rural households ( 138 ).…”
Section: Discussionmentioning
confidence: 98%
“…According to Sinclair et al, rural women had a higher prevalence of FI, which is in accordance with our subgroup analyses based on the region that indicated that the prevalence of FI was higher in rural areas [66.1% (95% CI: 58.8–73.4%)] compared to urban areas [47.1% (95% CI: 58.8–73.4%)] ( 136 ). Another study conducted by Sims et al found that there was FI and malnutrition among Indian rural women ( 137 ). In addition, Sansón-Rosas et al found high rates of FI in Colombian rural households ( 138 ).…”
Section: Discussionmentioning
confidence: 98%
“…A study in Madhya Pradesh, a part of the central region of India, asserts that there is a shallow dietary diversity and high food insecurity, which can be attributed to the high level of single and multimorbidity among women of the reproductive age in the region [42]. This is perhaps a consequence of the absence of dietary diversity and food security in India which varies substantially across the nation [42][43][44][45][46]. Hence, after decrypting the factors that play a pivotal role in increasing the prevalence of multimorbidity among women are the region, working status, age of an individual, BMI, the level of education.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, raising the income of families is equivalent to improving their ability to access a balanced and diversified diet. Taking into account the fact that poor people spend most of their income on food, an increase or decrease in = income can have immediate effects on household food security [19,28].…”
Section: Theoretical Aspectsmentioning
confidence: 99%